Sensor networks : 6th International Conference, SENSORNETS 2017, Porto, Portugal, February 19-21, 2017, and 7th International Conference, SENSORNETS 2018, Funchal, Madeira, Portugal, January 22-24, 2018, revised selected papers /: 6th International Conference, SENSORNETS 2017, Porto, Portugal, February 19-21, 2017, and 7th International Conference, SENSORNETS 2018, Funchal, Madeira, Portugal, January 22-24, 2018, revised selected papers. ([2019]) - Unknown
No abstract available